Kriteriji za izbor rastlinskih prehranskih dopolnil za prodajo v lekarni - Kreft, Samo (Farmacevtski vestnik, 2018)
food supplements, especially those with medicinal plants, are products whose quality depends on many factors. Some quality factors are defined by law and are controlled by state authorities, while others are left to market judgment. Since consumers are largely not professionally trained, it is reasonable that pharmacists help them to choose high quality supplements. In the assessment, they can use the declaration on the packaging and the accompanying instructions, or may require additional documentation from the manufacturer.
Keywords: certifikat; kakovost; označba izdelkov; Prehranski dodatki; varnost izdelkov; Zdravilne rastline